Push-Out Test on SCS sandwich composite members with various concrete cores and shear connectors - Chang, Jia Wei (Universiti Teknologi PETRONAS, 2021)
The development of Steel-Concrete-Steel1(SCS) sandwich composite construction has accelerated in recent decades. SCS members have been used as lightweight key components in buildings, bridges, and other structures in civil engineering applications because of its features and advantages. Slippage in SCS sandwich composite member could happen in between concrete and steel plates under compressive loading or in a column under axial load. As a result, the composite action could be reduced and thus decreasing the load-bearing capacity. This research is to explore the failure modes of the SCS specimens and to study the influences of various parameters such as concrete type and shear connector type on the interface behavior in SCS sandwich composite column by carrying out a series of push-out tests.